2009
DOI: 10.1590/s0074-02762009000900028
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease, adipose tissue and the metabolic syndrome

Abstract: Trypanosoma cruzi infection of the adipose tissue of mice triggers the local expression of inflammatory mediators and a reduction in the expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
(62 reference statements)
1
19
0
4
Order By: Relevance
“…In the present paper, we demonstrate that treatment with 15d-PGJ 2 reduces inflammatory infiltration and decreases the size of amastigote nests in the cardiac tissue of T. cruzi-infected animals. A previous study has demonstrated that T. cruzi infection leads to a reduced expression of adiponectin and PPAR-γ and that this reduction perpetuates the inflammatory phenotype found in CD (Nagajyothi et al 2009). Thus, the use of 15d-PGJ 2 to control the inflammatory response associated with CD may be useful.…”
Section: Discussionmentioning
confidence: 94%
“…In the present paper, we demonstrate that treatment with 15d-PGJ 2 reduces inflammatory infiltration and decreases the size of amastigote nests in the cardiac tissue of T. cruzi-infected animals. A previous study has demonstrated that T. cruzi infection leads to a reduced expression of adiponectin and PPAR-γ and that this reduction perpetuates the inflammatory phenotype found in CD (Nagajyothi et al 2009). Thus, the use of 15d-PGJ 2 to control the inflammatory response associated with CD may be useful.…”
Section: Discussionmentioning
confidence: 94%
“…Review of the current human studies as to whether T. cruzi infection leads to hyperglycemia and diabetes on the other hand, is inconclusive. For one, findings of hypoinsulinemia were variable, found in all Chagasic patient groups (Nagajyothi et al 2009; Oliveira et al 1993) or only among a sub-group of infected patients (Guariento et al 1993). In addition, decreased insulin secretion did not consistently correlate with increased prevalence of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors also report that it's an imbalance in the process of regulation between the pro and anti-inflammatory cytokines, increasing the chances of tissue damage for the person (Combs et al, 2005;Nagajyothi et al, 2009;Ferreira et al, 2011;Tanowitz et al, 2011;Nagajyothi et al, 2012).…”
Section: Clinical Formsmentioning
confidence: 99%